A 13-Year-Old Presenting With Recurrent Angioma Serpiginosum. Issue 5 (September 2018) - Bishara, Michael; Jiaravuthisan, Michael; Weinstein, Miriam
Background: Angioma serpiginosum (AS) is a rare vascular abnormality consisting of proliferation and dilation of superficial blood vessels in the skin. AS typically presents in the first 2 decades of life and remains stable with time. Case Summary: We report the case of a 13-year-old female with an acquired, recurrent erythematous lesion with serpiginous borders on her left upper arm. Over several years, the lesion reappeared then disappeared 12 to 15 times. At one point, she developed a tender red nodule within the lesion; consequently, a biopsy was taken, revealing dilated telangiectatic vessels in the dermal papillae with mild, focal extravasation of erythrocytes. Conclusion: This case demonstrates a lesion with suggestive clinical and histological features of AS. However, this may be the first case of recurrent AS with a symptomatic episode. This case may contribute to the expanding clinical spectrum of this interesting disease entity.